Calcite dissolution by mixing waters: geochemical modeling and flow-through experiments - E. SANZ; C. AYORA; J. CARRERA (Geologica Acta, 2011)
Dissolution of carbonates has been commonly predicted by geochemical models to occur at the seawater-freshwater mixing zone of coastal aquifers along a geological time scale. However, field evidences are inconclusive: dissolution vs. lack of dissolution. In this study we investigate the process of calcite dissolution by mixing waters of different salinities and pCO2, by means of geochemical modeling and laboratory experiments. Our calculations show that saturation is not always a good indicator of the real dissolution potential of the mixture. In a closed system, the maximum subsaturation occurs for mixing ratios of about 15%-salty, while the dissolved calcite is maximum for 50%. Dissolution is affected by carbonate speciation, and by the dependence of activity coefficients on salinity. Laboratory experiments confirmed a strong dependence of the dissolution on the mixing ratio and pointed out the critical role of CO2 variations at the local atmosphere. The maximum dissolution was observed for mixtures less than 17%-salty, which is attributed to the CO2 exchange between the reaction cell and the laboratory atmosphere. The reaction cell gains CO2 for mixtures less than 17%-salty and calcite dissolution is enhanced with respect to a closed system. The opposite also occurs for mixtures higher than 17% salty. Including CO2 exchange, the model consistently predicts the experimental results. Both calculations and dissolution experiments at different flow rates demonstrated a high sensitivity of the amount of calcite dissolved to minor variations of CO2 partial pressure of the local atmosphere. This could be relevant in field scale interpretations. CO2 pressure measurements in the field are not easy to obtain and could account for the different and “contradictory” field observations.